THE ROLE OF SURFACE SULFUR SPECIES IN THE INHIBITION OF PYRRHOTITE DISSOLUTION IN ACID CONDITIONS - EXPERIMENTAL OXIDATION OF PYRITE - Thomas J.E.; Jones C.F.; Skinner W.M.; Smart R.S.C. (My University, 1998)
Pyrrhotite, in anoxic acidic conditions, exhibits an induction period before rapid dissolution occurs. The length of the induction period is controlled by the amount of surface oxidation products on the mineral surface, acid strength, and temperature. During the induction period there is slow release of iron but little or no production of H2S. The induction period is best described as a period of inhibited dissolution, before the onset of H2S production and increased rate of iron release of at least 2 orders of magnitude. X-ray photoelectron spectroscopic (XPS) analysis of the acid-reacted surface shows the progress of the dissolution.Four stages of dissolution have been identified. (1) The immediate dissolution of an outermost layer of oxidised iron hydroxide/oxyhydroxide species and oxy-sulfur species. (2) Inhibited, diffusion limited dissolution during an induction period due to iron diffusion through the metal-deficient layer and oxidative dissolution of the polysulfide species. (3) Rapid, acid-consuming reaction of mono-sulfide species under nonoxidative or reductive conditions with production of H2S. (4) Inhibited dissolution due to reoxidation of the sulfide surface by oxidising solution species (i.e., Fe3+, residual oxygen) to produce polysulfide, elemental sulfur, and oxy-sulfur species.Dissolving synthetic pyrrhotite in similar, but aerated, acidic conditions, results in inhibited dissolution characterised by a lower rate of Fe release, minimal release of SO42- and no release of H2S . The XPS sulfur (S2p) spectrum shows sulfate and a form of elemental sulfur on the reacted surface. Only the first two stages of dissolution occur. The second stage differs in this case in that there is a plentiful supply of oxidising species (O2).Two reaction mechanisms are proposed for the dissolution of the iron sulfide lattice of pyrrhotite in acidic conditions. The mechanisms are oxidative and nonoxidative dissolution. Two distinct activation energies are associated with the two regimes. A lower activation energy corresponds to inhibited dissolution with no production of H2S. A t1/2 rate law describes dissolution in air saturated solutions and supports diffusion controlled dissolution under these conditions. A higher activation energy corresponds to rapid dissolution with H2S production. The mechanism of dissolution is determined by the state of the surface, particularly the sulfur species.